Female Violence and the Force of Trauma in “The City of Sorrow” - Chhetry, Tek Bahadur; Kandel, Tika Ram (Nepal Journal of Multidisciplinary Research, 2021)
The focus of this study is on the area of traumatic affect. Intizar Hussain represents female violence and displacement during India’s partition in neutral way keeping identity politics away. Such a study is important to observe trauma literature in the light of pure affect and critically evaluate the trauma literatures which are found to have been valorizing one side and demonizing others for the vested interest. The research approach adopted in this study includes literature review of women violence during the partition and a brief comparison of ‘The City of Sorrow ‘with ‘Train to Pakistan’ to identity two different approaches of representing trauma. The findings from this study provide an insight on pure affect evoked by Hussain. The conclusion drawn from this study sheds light on how the hatred and the violence create the vicious circle of trauma and the chain can be minimized in trauma art by ‘moral working through’, keeping identity politics at bay.